Equilibrium Income Inequality among Identical Agents - Freeman, Scott (Journal of Political Economy, 1996)
The paper offers a theory of income differences in which income inequality exists and persists despite identical tastes and talents. Teams of unskilled labor supervised by schooled managers produce goods with increasing returns to scale. Agents are assumed unable to borrow to fund the human capital investment needed to become managers. Despite ex ante identical agents, the model displays the following equilibrium phenomena: (i) risk-averse agents accept fair gambles, implying an unequal ex post distribution of unearned income; (ii) agents agree to publicly subsidize education, although those receiving the subsidy have the highest material wealth; and (iii) income and educational differences are perpetuated from generation to generation.